The platform politics of hateful play on Twitch - Phipps, Elizabeth; Murphy, David; Jarrett, Joshua (AoIR Selected Papers of Internet Research, 2026)
In this essay, we argue that the term “hate raiding” requires clearer definition within digital platform studies scholarship to combat efforts to apply the term to anti-brand protests (Murphy & Jarrett 2024). To render our definition, we use critical game studies scholarship (Trammell 2023, Giddings & Harvey 2018) to analyze how the conditions of reciprocity and play on Twitch.tv (Twitch) produce the conditions for hate raids to occur as playful (Scholl 2024), non-antisocial behavior. In other words, we insist that hate raids should not be viewed as transgressive acts of play, or morally motivated forms of networked harassment (Marwick 2021), arguing that this type of harassment is a consequence of ludic economics in general (Giddings & Harvey) and the sociality cultivated on Twitch in particular. Through thoughtful discursive, infrastructural, and rhetorical analysis of Twitch.tv’s branding and platform governance, we demonstrate that hate raiding is not a bug, but in fact a feature of the live streaming platform.